2014
DOI: 10.1016/j.otpol.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptors on peripheral blood white cells in acute otitis media

Abstract: Peripheral blood monocytes are characterized by increased expression of TLRs in the course of recurrent AOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Data from the literature have shown a differential TLR4 or CD14 expression among different types of immune cells including lymphocytes and granulocytes [25]. In our hands, we found that TLR4/CD14 are expressed in vascular cells from human or mouse origin (data are not shown).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 52%
“…Data from the literature have shown a differential TLR4 or CD14 expression among different types of immune cells including lymphocytes and granulocytes [25]. In our hands, we found that TLR4/CD14 are expressed in vascular cells from human or mouse origin (data are not shown).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 52%
“…A comparison of TLR4 expression in lymphocytes, monocytes, and granulocytes in peripheral blood from children with recurrent or persistent AOM showed that TLR4 expression is high in monocytes and low in lymphocytes. These results suggest that an increase in TLR4 in peripheral blood monocytes is involved in the pathogenesis of AOM [20]. An analysis of DNA samples from 348 children with a history of two or more AOM episodes and 463 healthy adults showed that the TLR4 299A/A genotype was associated with an otitis-prone condition [39].…”
Section: Tlr4mentioning
confidence: 86%
“…A study on TLR1 expression in relation to otitis media that compared the expression of TLR1 in the peripheral blood of recurrent or persistent AOM children with that of a normal pediatric control group showed that expression of TLR1 in monocytes was higher in the AOM group than in the normal control group [20]. In another study, in which OME children who had undergone ventilation tube insertion were classified into otitis-prone and non-otitis-prone groups, a comparison of TLR1 expression in middle ear effusion of both groups showed a trend toward higher expression of TLR1 mRNA in the otitis-prone group [21].…”
Section: Tlr1mentioning
confidence: 99%
See 2 more Smart Citations